INSTAGRAM STORY SEBAGAI MEDIA PEMBELAJARAN KETERAMPILAN MENULIS BAHASA JERMAN KELAS X SEMESTER I - Muskini, Desti Rina; Wahyuningsih, Fahmi (LATERNE, 2021)
Writing skills are the most complex productive skills compared to the other three language skills: reading, listening and speaking (Nurgiyantoro, 1987: 270). Especially in learning German at school as a second foreign language after English. German is unique in its grammar by allowing changes to verbs according to the pronoun used, the existence of articles on each noun, and nouns that must always use capital letters at the beginning. These are important points needed in writing skills, especially at beginner level writing (Wassid and Sunendar, 2008: 292). With these facts, efforts are needed to help German learners practice their writing skills in an interesting and innovative way. This article uses a literature study method with a qualitative approach. The object studied was Instagram Story and analyzed using theories of writing skills, learning media, and Syllabus for German Language Subjects class X Semester I Curriculum 2013 (Kemendikbud) for the material. This article aims to provide a suggestion of ideas about innovation and reference for learning media to practice German writing skills. The advantages found in this media are: 1) students can practice about the material that has been studied independently, 2) efficient media, because educators can provide the writing exercises anytime and anywhere, 3) students can also do the exercises anytime and anywhere, 4) a fun learning media, because it can be done while socializing, and 5) promote and educate other Instagram users about the German language. While the disadvantages are: 1) requires an internet connection, 2) The template in this article is only designed for one theme, and 3) if it is to be used for another materials, a redesign is required.